2010
DOI: 10.1111/j.1365-2249.2010.04232.x
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces maturation-arrested dendritic cells that expand regulatory T cellsin vitroandin vivo

Abstract: SummaryDendritic cells (DC) and regulatory T cells (Tregs) are vital to the development of transplant tolerance. Curcumin is a novel biological agent extracted from Curcuma longa (turmeric), with anti-inflammatory and anti-oxidant activity mediated via nuclear factor (NF)-kB inhibition. We investigated the immunomodulatory effects of curcumin on human monocyte-derived and murine DC. Human monocyte-derived DC (hu-Mo-DC) were generated in the presence (CurcDC) or absence (matDC) of 25 mM curcumin, and matured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 75 publications
(95 reference statements)
6
36
0
2
Order By: Relevance
“…The expression of negative regulatory molecules PD-L1 and PD-L2 were also downregulated. IL-12p40 mRNA expression and biologically active IL-12 secretion by CurcDC were significantly reduced, while they could produce IL-10 as before [84]. These data are consistent with the observed suppression of NF-κB nuclear activity by curcumin [35,38].…”
Section: Curcuminsupporting
confidence: 94%
See 1 more Smart Citation
“…The expression of negative regulatory molecules PD-L1 and PD-L2 were also downregulated. IL-12p40 mRNA expression and biologically active IL-12 secretion by CurcDC were significantly reduced, while they could produce IL-10 as before [84]. These data are consistent with the observed suppression of NF-κB nuclear activity by curcumin [35,38].…”
Section: Curcuminsupporting
confidence: 94%
“…These data are consistent with the observed suppression of NF-κB nuclear activity by curcumin [35,38]. The allostimulatory activity of CurDC and IFN-γ production in the responding T cells was reduced [84]. It can be concluded that CurcDC promotes FoxP3 + Tregs capable of inducing regulatory function on naive T cells.…”
Section: Curcuminsupporting
confidence: 89%
“…Curcumin has immunomodulatory, anti-proliferative, antimicrobial, anti-inflammatory and antioxidant effects and hence has potential therapeutic value in IRI. Curcumin is insoluble in water with a high level of octanol: water partition coefficient (logPow= 3.29), which limits its application as an orally delivered agent [4-7]. Earlier studies determining the effectiveness of curcumin on IR injury in animal models have used oral delivery with slight functional salvage [8-10].…”
Section: Introductionmentioning
confidence: 99%
“…187,188 Curcumin treatment of LPS-matured DC arrests their maturation into a tolerogenic phenotype that preferentially promotes the suppressive function of T reg cells. 189 Oral treatment with curcumin alleviates intestinal inflammation by inhibiting proinflammatory Th1 cytokines. 183 However, curcumin has never been investigated in ocular inflammation.…”
Section: What Can a Rabbit Model Teach Us About The Immunopathology Omentioning
confidence: 99%